Lexicografia i models lingüístics: les teories lingüístiques i el lèxic - Badia, Toni (Caplletra. Revista Internacional de Filologia, 2015)
In this paper a discussion is offered of the relation between linguistic theories and lexica. It is shown that linguistic theories imply particular approaches to the lexicon from which particular ways of conceiving the lexicographer’s work can be inferred. To this end a few linguistic theoretical models are examined and their idea of the lexicon is reviewed. Obviously it is beyond the scope of this paper to discuss the approach to lexicon of all different linguistic theories developed during this century. Consequently a few models have been chosen for examination which nonetheless are quite representative of the main phases of the recent history of linguistics. After a very short discussion of the characteristics of traditional grammar, the paper starts the discussion with structuralism and then moves over to the examination of some of the linguistic theories that can be broadly considered «generative»; three basic stages in the development of Chomsky’s approach are reviewed, i.e., the ones represented by Syntactic structures, Aspects of the theory of syntax, and Lectures on government and binding; and finally the discussion ends with an examination of LFG (Lexical-functional grammar) and HPSG (Head-driven phrase structure grammar) which are two of the emerging theories are that have originated in the linguistic millieus most influenced by computational linguistics.